Documents Concerning Ankara During the Second World War in the Republic Archive of Prime Ministry 1939-1945 - Çağatay Benhür (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
The Second World War is the greatest conflict that the world ever has seen, is a research field that is focused by many scientists from various fields. Thousands of studies have been carried out in the world, in the fields of social sciences, natural sciences and health sciences but not enough research focused about Turkey during the Second World War. The aim of this paper is to study the Second World War documents in Ankara in the Republic Archive of Prime Ministry; To make a new addition to the Turkey-based Second World War scholarship, to contribute to the social sciences studies of the same field in the world, and to roughly classify the archived documents in the Republic Archive of Prime Ministry. Future studies are expected to make use of this classification. The desire to put all these aims into practice in Ankara constitutes the second aim of this study. The Second World War was the most destructive war throughout the history. Turkey, had not attended the war but affected by it. When the war started, Ankara was a newly developed 16 years old capital city and had important tasks as Turkey’s administration centre. In this work, catalogue documents in the Republic Archive of Prime Ministry about Ankara during the Second World War have been studied and sorted. Republic Archive of Prime Ministry catalog; is a storage with large volumes and variety in the form of 15 fund areas consisting of various fields and a common information pool of 169 different institutions. For this reason, the scans made in the aforementioned catalogs provide results from a rich information network and provide significant contributions to the research to be carried out. The focus of the research is to contribute to the social studies based on works in Turkey during the Second World War. Moreover, new statistical data would be a contribution to the national data system. International data bases and indexing of the current archived documents will pave way for new researches. In this sense and especially for Ankara, the course of Turkey during the war has tried to be figure out. 1303 archive documents with military and civil contents have been evaluated and 62 different topics have been classified. This classification will also help others who will do research in this area and help to enlight the situation of Ankara during the Second World War